The Posttraumatic Occlusion of the Vertebral Artery - Cornelia Tudorache; Adriana Moldovanu; Anda Esanu; E. Moldovanu; Carmen Gherman; C. Ichim; C. Popescu; M. Dabija; Danisia Haba (Romanian Neurosurgery, 2010)
We investigate radiographic features of vertebral artery injury/occlusion associated with nonpenetrating cervical spine trauma and to demonstrate the importance of the CTA in high-risk cases. With the popularization of CTA (Computed Tomography Angiography) and MRA (Magnetic Resonance Angiography), vertebral artery injury has been a common complication of cervical spine trauma. The occlusion of the vertebral artery secondary to non-penetrating trauma of the cervical spine (fractures and/dislocations) can be found in approximately 20% of the cases. Vertebral artery occlusion was rarely symptomatic because of sufficient collateral blood supply through not only contralateral vertebral artery but also the circle of Willis.